Control interno y su incidencia en la gestión administrativa del GAD del cantón Pichincha en el período 2014. - Chanalata Tuárez, María José (2016)
This research was conducted in the Pichincha Canton, in the Autonomous Decentralized Municipal Government of the canton Pichincha. The research phase lasted 120 days, whose overall objective is to examine the INTERNAL CONTROL AND ITS IMPACT ON ADMINISTRATIVE MANAGEMENT OF Pichincha Canton GAD IN THE PERIOD 2014. Assessing whether there are processes that meet the requirements demanded for internal control; as investigating the efficiency, effectiveness and compliance processes for Administrative Management; to analyze how they are handled each of the processes for influencing the administration in the 2014 period. It applied internal control questionnaire related to the administration of the GAD Pichincha was applied, and accurate and reliable information was obtained. This study and evaluation of internal control determined that the UATH not developed the corresponding planning from previous years to 2014. Internal control tools allow us to observe the lack of management UATH in the development of a Human Resource Planning, contravening duties and powers of the Organic Law of the Comptroller General. Hiring occasional services in the state exceeded 20% of the permitted, this contract was done without prior analysis and monitoring. The company did not have a manual Sorter Since, containing standardized rules allow analyze, describe, assess and classify the positions where they know the tasks, responsibilities, and requirements of all positions for effective compliance and safe corporate objectives